GnRH analog is ineffective in increasing adult height in girls with puberty onset after 7 years of age: A systematic review and meta-analysis - Franzini, I. A. [UNESP]; Yamamoto, F. M. [UNESP]; Bolfi, F. [UNESP]; Antonini, S. R.; Nunes-Nogueira, V. S. [UNESP] (Oxford University Press (OUP), 2018)
Objective: We assessed the effectiveness of puberty blockade with a gonadotropin-releasing hormone (GnRH) analog in increasing adult height (AH) in girls with puberty onset between 7 and 10 years of age. Methods: We performed a systematic review and included controlled studies in which girls with early puberty (EP) were assigned to the GnRH analog or no treatment groups. The primary outcome analyzed was AH. Search strategies were applied to the MEDLINE, EMBASE, LILACS and CENTRAL databases. Results: We identified 1514 references, and six studies fulfilled our eligibility criteria. Two studies were randomized and four were not randomized. At the baseline of each trial, height, chronological age, bone age, predicted AH (PAH) and target height (TH) were equal between the groups. All studies used intramuscular triptorelin every 28 days in the intervention groups. The mean duration of the therapy was 2 years. Meta-analysis of AH among the six studies (comprising 332 girls) showed no significant difference between the groups (mean difference = 0.50 cm, 95% confidence interval = −0.72 to 1.73 cm, I2 = 0%). In a sub-group analysis based on PAH (<155 cm and <TH; <TH, but >155 cm and equal to TH), there was no difference in average AH between the groups. The quality of evidence according to the Grading of Recommendations Assessment, Development and Evaluation approach was low. Conclusion: We found no evidence from controlled experimental and observational studies that compared with no treatment, the use of GnRH analogs improved AH in girls with EP.